ANALISIS FAKTOR- FAKTOR KEJADIAN PREEKLAMSIA DI RSUD PRAYA KABUPATEN LOMBOK TENGAH - Elly Sustiyani; Hasrun Ningsih (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Maternal mortality Refers to death due to complications from pregnancy or childbirth. According to WHO, in 2015 the number of MMR was 216 deaths per 100,000 live births. More than 800 mothers die every day due to complications of pregnancy and childbirth caused by bleeding (27%), hypertension or preeclampsia (14%), infection (11%), abortion (8%), embolism (3%), indirect death (28%) and immediate death (10%). UNICEF (2020). Women (2018) Pregnancy is a physiological process but many complications can cause high maternal mortality, one of which is preeclampsia. Approximately 13% of women aged 15 - 20 years have a high risk for both mother and fetus, women aged 35 years show a significant increase in the incidence of hypertension or preeclampsia. Data were collected on Medical Record Division in General Praya Regional General Hospital, Central Lombok Regency on February to November 2019. The subject of research a number of 65 cases of pre eclampsia ( as the case group ) and 65 cases did not pre eclampsia ( as the control group ). Data analysis is univariate, bivariate and multivariate analyzes. Variables significantly associated with the incidence of pre eclampsia is a parity, age, and birth interval variable..Variabel most dominant pre eclampsia is a parity variable (OR = 91,47) means women in first parity and over 4 parity have a chance 91,47 times more likely to experience pre eclampsia compared with women in second till fourth parity. Advise : need a family planning and increase to examination for antenatal care on pregnancy so can be detection sign and symptom base on early.